Naloxone Facilitates Contextual Learning and Memory in a Receptor-Independent and Tet1-Dependent Manner - Meng, Fei; Li, Yuan; Sun, Hao; Li, Changpeng; Li, Qian; Law, Ping-Yee; Loh, Horace H.; Liang, Lining; Zheng, Hui (Cellular and molecular neurobiology, 2021)
Opioids, like morphine and naloxone, regulate the proliferation and neuronal differentiation of neural stem cells (NSCs) in a receptor-independent and ten-eleven translocation methylcytosine dioxygenase (TET1)-dependent manner in vitro. Whether naloxone regulates hippocampal NSCs and contextual learning in vivo in a similar manner was determined. Naloxone infusion increased the Ki67 and Doublecortin positive cells in subgranular zone of wild type mice, which suggested the increased proliferation and differentiation of hippocampal NSCs in vivo and was consistent with the in vitro functions of naloxone. In addition, naloxone infusion also facilitated the contextual learning and memory of wild type mice. To determine the contribution of μ-opioid receptor (OPRM1) and TET1 to these functions of naloxone, several types of knockout mice were used. Since Tet1 −/− mice have high deficiency in contextual learning and memory, Tet1 +/− mice were used instead. The abilities of naloxone to regulate NSCs and to facilitate contextual learning were significantly impaired in Tet1 +/− mice. In addition, these abilities of naloxone were not affected in Oprm1 −/− mice. Therefore, naloxone facilitates contextual learning and memory in a receptor-independent and Tet1 -dependent manner, which provides new understanding on the receptor-independent functions of opioids.